Calcium Sensors as Key Hubs in Plant Responses to Biotic and Abiotic Stresses - Ranty, Benoît; Aldon, Didier; Cotelle, Valérie; Galaud, Jean-Philippe; Thuleau, Patrice; Mazars, Christian (Frontiers in Plant Science, 2016)
The Ca2+ ion is recognized as a crucial second messenger in signalling pathways coupling the perception of environmental stimuli to plant adaptive responses. Indeed, one of the earliest events following the perception of environmental changes (temperature, salt stress, drought, pathogen or herbivore attack) is intracellular variation of free calcium concentrations. These calcium variations differ in their spatio-temporal characteristics (subcellular location, amplitude, kinetics) with the nature and strength of the stimulus and, for this reason, they are considered as signatures encrypting information from the initial stimulus. This information is believed to drive a specific response by decoding via calcium-binding proteins. Based on recent examples, we illustrate how individual calcium sensors from the calcium-dependent protein kinase (CPK) and calmodulin-like protein (CML) families can integrate inputs from various environmental changes. Focusing on members of these two families, shown to be involved in plant responses to both abiotic and biotic stimuli, we discuss their role as key hubs and we put forward hypotheses explaining how they can drive the signalling pathways towards the appropriate plant responses.